2017
DOI: 10.21873/invivo.11184
|View full text |Cite
|
Sign up to set email alerts
|

Balneotherapy in Psoriasis Rehabilitation

Abstract: After completing the 3-week-long spa therapy based rehabilitation, both PASI score and CRP levels showed improvement of psoriasis. The complex spa therapy used during the rehabilitation is an effective tool to reduce the symptoms of psoriasis and improve the patient's well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Both 2 w balneotherapy and BPT groups brought greater psoriasis amelioration with reduction in both PASI score and BSA. Péter et al, 2017 [ 88 ] Balneotherapy Prospective single-arm cohort 3 w 80 35M/45F 63.7 NS N/A PASI, CRP level After therapy, both PASI and CRP levels presented significant improvement. Tabolli et al, 2009 [ 89 ] Balneotherapy and BPT Prospective, non-randomized 2 w 111: 66 Therapy 45 Control 67M/24F >18 y 25 < 10 y; 81 > 10 y BPT vs. Comano balneotherapy alone SAPASI, Skindex-29, GHQ-12, SF-36 A decrease >50% after therapy in SAPASI 50 score was attained by 42% and 37% of patients in the BPT and BT groups, correspondingly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both 2 w balneotherapy and BPT groups brought greater psoriasis amelioration with reduction in both PASI score and BSA. Péter et al, 2017 [ 88 ] Balneotherapy Prospective single-arm cohort 3 w 80 35M/45F 63.7 NS N/A PASI, CRP level After therapy, both PASI and CRP levels presented significant improvement. Tabolli et al, 2009 [ 89 ] Balneotherapy and BPT Prospective, non-randomized 2 w 111: 66 Therapy 45 Control 67M/24F >18 y 25 < 10 y; 81 > 10 y BPT vs. Comano balneotherapy alone SAPASI, Skindex-29, GHQ-12, SF-36 A decrease >50% after therapy in SAPASI 50 score was attained by 42% and 37% of patients in the BPT and BT groups, correspondingly.…”
Section: Resultsmentioning
confidence: 99%
“…Other locations that have climatotherapeutic or balneotherapeutic (bathing in hot springs) effects are in the Black Sea, Nord Sea, Baltic Sea, Canary Islands, Kangal Hot Springs in Turkey, or the Blue Lagoon in Iceland, but the evidence regarding each of these sites is lacking when compared to the Dead Sea [11,18,70,110,111]. Balneotherapy alone or in combination with standard treatment or phototherapy has repeatedly proven to be more effective than standard treatment alone [23,[85][86][87][88][89]. Geothermal sea water balneotherapy and narrowband UVB (NB-UVB) light therapy is apparently more effective in attaining clinical and histological amelioration, results in longer remission time and allows for lower UV doses than NB-UVB therapy alone [21].…”
Section: Balneotherapy and Climatotherapymentioning
confidence: 99%
“…Recently, the clinical trials reported in the Cochrane library focused on the effects of balneotherapy on chronic painful diseases, as rheumatoid arthritis for example (Verhagen et al, 2015(Verhagen et al, , 2007. Extensive research related to curative treatments of chronic dermatological diseases like ichthyosis, psoriasis and atopic dermatitis by hydrotherapy has been investigated since it has significant benefits on the quality of patients' lives (Bodemer et al, 2011;Gambichler et al, 2001Gambichler et al, , 2000Péter et al, 2017). Huang et al (2018) have recently published a review on the clinical applications of TSW on the skin, especially their immunomodulatory effect on inflammatory and autoimmune dermatologic diseases.…”
Section: Composition Of Thermal Spring Watersmentioning
confidence: 99%
“…Previous studies have shown the beneficial effects of balneotherapy in musculoskeletal (chronic low back pain, rheumatoid arthritis, etc), gynecological, and dermatological conditions (psoriasis in particular); peripheral vascular disease; fibromyalgia; and many other disorders (Ayán et al 2017;Bender et al 2014;Fioravanti et al 2018;Hanzel et al 2018;Karagülle et al 2018;Péter et al 2017).…”
Section: Introductionmentioning
confidence: 99%